An Investigation Into The Drag Increase on Roughen Surface due to Marine Fouling Growth - A. K. Yusim; I. K. A. P. Utama (IPTEK The Journal for Technology and Science, 2025)
Marine biofouling attached to underwater ship hull has caused problems for many years to ship operators. It has been reported to increase the total drag thus can reduce the speed of ship and disturb the overall operation of marine vehicles. Changes laminar to turbulent flow becomes fast when passing through rough ships surface. The current study models the growth of marine fouling for one year periods basis on general cargo vessel. The methods have been used in this studied was model scale 1 : 53. The use of smooth model is also included in order to analyses the difference between the two conditions. Two models of the hull roughness are regular and irregular roughness. The modeling of roughness using sand with a specific size and have been scaled. The results show that an increase in skin friction drag of about 41% per year for biofouling spread not evenly at wetted surface area (WSA).